Perancangan Sistem Pendukung Monitoring Kinerja Program Studi Dengan Metode Balanced Scorecard Studi Kasus: Prodi Di Fakultas Teknik UKDC - Albertus Daru Dewantoro; Nehemia Dwi April Riyanto; Antonius Yan Sheva Christiano; Citra Rahayu Kumaladewi (Industrial & System Engineering Journals (ISEJOU), 2022)
The activity of implementing the performance evaluation of study programs in tertiary institutions aims to improve internal quality in a sustainable manner. The performance evaluation process requires a gradual process, namely the performance monitoring process. Evaluation and monitoring of study program performance are generally implemented in the implementation of education, research, and community service to improve study program performance. Therefore, the priority of the main performance indicators of study programs in the Faculty of Engineering is determined by referring to the Chancellor's Regulation No. 03/PR/2022, classifies the main performance indicators of the Faculty of Engineering study program based on the dimensions of the balanced scorecard, and designs a work program monitoring spreadsheet to support KPI achievement. The research also aims to identify KPIs in four stages: customer perspective, financial perspective, business process perspective, and learning and growth perspective. The University has prioritized the 1st, 2nd, 4th, 6th and 7th performance indicators. Regulation of the Dean of the Faculty of Engineering No. 143/UKDC.1/A.01/XI/2022 as a reference in setting KPIs, this document has succeeded in formulating 22 main performance indicators and 5 additional performance indicators. Prioritized performance indicators are then made into a spreadsheet-based performance form which is useful in implementing performance monitoring